Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Chapter 4 - Graphs of the Circular Functions - Section 4.3 Graphs of the Tangent and Cotangent Functions - 4.3 Exercises - Page 172: 52


$cot(-x) = -cot~x$

Work Step by Step

$cot(-x) = \frac{cos~(-x)}{sin~(-x)}$ $cot(-x) = \frac{cos~(x)}{-sin~(x)}$ $cot(-x) = -\frac{cos~(x)}{sin~(x)}$ $cot(-x) = -cot~x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.